2016
DOI: 10.5713/ajas.16.0281
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Milk Fatty Acid Composition for Production of Functional Milk by Dietary Phytoncide Oil Extracted from Discarded Pine Nut Cones (Pinus koraiensis) in Holstein Dairy Cows

Abstract: This study was conducted to examine the effects of adding phytoncide oil extracted from Korean pine nut cone byproduct to the diet of dairy cows on milk yield and compositions, fatty acid characteristics, complete blood count and stress response. A total of 74 Holstein cows were used for 30 days and divided into two groups. Each group was given a basal diet (C) or an experimental diet containing phytoncide additives at 0.016% (T) in feed. The results showed that phytoncide feeding had no effect on milk yield. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…The proportions of CLA produced in milk depend mainly on the diets that are fed (Kim et al 2016). This can be explained by use of food by microbes in the rumen and the modification of the proportions of acetate and propionate in the rumen which reflects on the proper digestion of the fibers in the presence of Moringa oleifera in the ration (Belhi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The proportions of CLA produced in milk depend mainly on the diets that are fed (Kim et al 2016). This can be explained by use of food by microbes in the rumen and the modification of the proportions of acetate and propionate in the rumen which reflects on the proper digestion of the fibers in the presence of Moringa oleifera in the ration (Belhi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The results on fatty acid compositions of the oils herein studied demonstrated the potential of the enzyme pool utilized to produce concentrates containing high amounts of essential fatty acids, important for human health. Omega 3 such as a-linolenic acid (C18:3) and omega 6 such as linoleic acid (C18:2) are essential fatty acid because mammals are unable to metabolically introduce double bonds at positions omega 3 and 6 of fatty acids carbonic chains [29]. Therefore, the source of these nutrients comes exclusively from food.…”
Section: Resultsmentioning
confidence: 99%
“…Lopez et al (2008) reported about 1.5% 23:0 in MFGM of cream. Park et al (2014), Schwendel et al (2015), Frelich et al (2009), and Kim et al (2016) also reported 23:0 in milk fat samples. It is also interesting that the BCFA were primarily found in the NL band.…”
Section: Fatty Acid Profile Of the Fractionated Pl Productsmentioning
confidence: 89%